Adenosine A2A Receptor Activation Regulates Niemann–Pick C1 Expression and Localization in Macrophages - Adrienn Skopál; Gyula Ujlaki; Attila Tibor Gerencsér; Csaba Bankó; Zsolt Bacsó; Francisco Ciruela; László Virág; György Haskó; Endre Kókai (Current Issues in Molecular Biology, 2023)
Adenosine plays an important role in modulating immune cell function, particularly T cells and myeloid cells, such as macrophages and dendritic cells. Cell surface adenosine A2A receptors (A2AR) regulate the production of pro-inflammatory cytokines and chemokines, as well as the proliferation, differentiation, and migration of immune cells. In the present study, we expanded the A2AR interactome and provided evidence for the interaction between the receptor and the Niemann–Pick type C intracellular cholesterol transporter 1 (NPC1) protein. The NPC1 protein was identified to interact with the C-terminal tail of A2AR in RAW 264.7 and IPMФ cells by two independent and parallel proteomic approaches. The interaction between the NPC1 protein and the full-length A2AR was further validated in HEK-293 cells that permanently express the receptor and RAW264.7 cells that endogenously express A2AR. A2AR activation reduces the expression of NPC1 mRNA and protein density in LPS-activated mouse IPMФ cells. Additionally, stimulation of A2AR negatively regulates the cell surface expression of NPC1 in LPS-stimulated macrophages. Furthermore, stimulation of A2AR also altered the density of lysosome-associated membrane protein 2 (LAMP2) and early endosome antigen 1 (EEA1), two endosomal markers associated with the NPC1 protein. Collectively, these results suggested a putative A2AR-mediated regulation of NPC1 protein function in macrophages, potentially relevant for the Niemann–Pick type C disease when mutations in NPC1 protein result in the accumulation of cholesterol and other lipids in lysosomes.